2016
DOI: 10.7717/peerj.2520
|View full text |Cite
|
Sign up to set email alerts
|

A transcriptomic scan for potential candidate genes involved in osmoregulation in an obligate freshwater palaemonid prawn (Macrobrachium australiense)

Abstract: BackgroundUnderstanding the genomic basis of osmoregulation (candidate genes and/or molecular mechanisms controlling the phenotype) addresses one of the fundamental questions in evolutionary ecology. Species distributions and adaptive radiations are thought to be controlled by environmental salinity levels, and efficient osmoregulatory (ionic balance) ability is the main mechanism to overcome the problems related to environmental salinity gradients.MethodsTo better understand how osmoregulatory performance in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 62 publications
0
37
0
Order By: Relevance
“…In freshwater prawn Macrobrachium rosenbergii, change in salinity has showed a direct or indirect effect on the respiratory metabolism, mortality, growth, and even immune response later (Cheng and Chen 2000;Moshtaghi et al 2016). To date, extensive studies have been conducted on a number of fish species to investigate tissuespecific functional roles of AQPs under different salinity environments (Cutler and Cramb 2000;Watanabe et al 2005;Giffard-Mena et al 2007;Kim et al 2010;Choi et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In freshwater prawn Macrobrachium rosenbergii, change in salinity has showed a direct or indirect effect on the respiratory metabolism, mortality, growth, and even immune response later (Cheng and Chen 2000;Moshtaghi et al 2016). To date, extensive studies have been conducted on a number of fish species to investigate tissuespecific functional roles of AQPs under different salinity environments (Cutler and Cramb 2000;Watanabe et al 2005;Giffard-Mena et al 2007;Kim et al 2010;Choi et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Invasion of freshwater can involve a multiplicity of complex adaptive responses including physiological, biochemical, mechanical, molecular and diverse environmental (phenotypic) traits (Wray, 2013;Moshtaghi et al, 2016). It is presumed that adaptations are a response to specific environmental conditions and are propagated by evolutionary forces.…”
Section: Crustacean Taxa In Evolutionary Studiesmentioning
confidence: 99%
“…Thus, prolonged however, crustacean osmoregulation predominantly involves ion balance via active uptake or secretion, as well as maintaining composition and concentration of hemolymph and urine (Barman et al, 2012;McNamara and Faria, 2012). It has been observed that freshwater crustaceans typically expend more energy for osmoregulation compared with comparable marine or brackish water species (Moshtaghi et al, 2016). Therefore, external salinity is one of the most important abiotic factors that can influence natural distributions, abundance, general physiology and wellbeing of aquatic crustaceans.…”
Section: Crustacean Taxa In Evolutionary Studiesmentioning
confidence: 99%
See 2 more Smart Citations